Patriotism or proletarian universalism. The place of the world in Colombian workerism and socialism, 1904-1930 (2013)
What is the role of external agents and dynamics in the introduction of a political movement in a country like Colombia? Can an intense connection with the outsideworld be read as a sign of the successful modernization of political discourses and practices? This article inquires into the position of workerist and socialist groups in the beginning of the XX century with respect to the outside world, that is, how they deined the Nation to which they aspired, and what place they gave to the universeas larger context. Findings show that in a irst stage, political activists of the working classes maintained scarce relations with Europe and United States, reafirming their search for greater equality as part of the vindication of the Nation. In a further stage, however, socialists rejected the Nation, building their hopes in the direction of a communist universalism, which put them into extended contact with what was  considered the matrix for a new humanity, at the cost of alienating the sympathy of the people they intended to represent.